2007
DOI: 10.1111/j.1464-410x.2007.07210.x
|View full text |Cite
|
Sign up to set email alerts
|

Bladder carcinoma among live‐donor renal transplant recipients: a single‐centre experience and a review of the literature

Abstract: OBJECTIVES To present our experience with bladder cancer among a renal transplant population and to review critically the relevant literature. PATIENTS AND METHODS In all, 1865 renal graft recipients were followed for a mean (sd) of 6.5 (5) years. Seven recipients (all men) developed a urothelial bladder tumour. The stage and grade of the tumours were determined. The method of the treatment was selected on the basis of the tumour characteristics and graft function. Patients were regularly followed; the endpoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 37 publications
2
29
1
3
Order By: Relevance
“…As found in this study and in others [12], an overwhelming majority of patients with urothelial cancer presented with gross hematuria. However, despite strict follow-up guidelines, many of the patients in the aforementioned studies still presented with advanced and aggressive disease, suggesting immunosuppression in solid organ recipients is associated with rapid progression of cancers [1].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…As found in this study and in others [12], an overwhelming majority of patients with urothelial cancer presented with gross hematuria. However, despite strict follow-up guidelines, many of the patients in the aforementioned studies still presented with advanced and aggressive disease, suggesting immunosuppression in solid organ recipients is associated with rapid progression of cancers [1].…”
Section: Discussionsupporting
confidence: 56%
“…The incidence in a recent French study was 0.4% [11]. An Egyptian report found 7 bladder cancers of 1,865 patients, following renal transplantation for an incidence of 0.4%, with a strong correlation with previous bilharzial infection [12]. As far as presentation at cancer diagnosis, most patients in our study were found to have advanced disease and many were metastatic at presentation.…”
Section: Discussionmentioning
confidence: 83%
“…El tratamiento de los tumores vesicales no músculo-invasivos en la población trasplantada aún no está consensuado, aceptándose la resección transuretral más quimioterapia endovesical como la terapia de elección 42 . Sin embargo, algunos autores como Kamal et al 43 sugieren que el uso en estos pacientes de la terapia con bacilo de CalmetteGuérin como inmunoterapia coadyuvante estaría indicada en algunos tumores, ya que disminuiría las recurrencias y mejoraría la supervivencia libre de enfermedad. Sin embargo, puede plantear problemas y podría conducir a una infección tuberculosa severa.…”
Section: Discussionunclassified
“…A los tumores vesicales músculo-invasivos se les realizó una cistectomía radical con derivación tipo Bricker, y en todos ellos se pudo conservar el trasplante. Algunos autores como Kamal et al 43 y Lang et al 44 sugieren que se puede realizar una reconstrucción con una vejiga ortotópica; estos autores no encontraron diferencias en cuanto a morbilidad ni mortalidad cuando realizaron esta técnica; si bien, el procedimiento tiene una mayor dificultad y sólo se debería plantear en los pacientes con un injerto renal en perfecto funcionamiento. Además, observaron que la afectación del riñón y el uréter del donante no suelen presentar recidivas o tumores uroteliales.…”
Section: Discussionunclassified
“…Bladder cancer is a far less common disease than skin cancer, and thus it is not surprising that cohort studies would observe few if any cases (Master et al, 2004;Kamal et al, 2007). An exception was a Taiwanese study that reported bladder cancer as the most common type of post-transplant malignancy with an incidence of 4.1% among kidney transplant recipients (Wu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%